2020
DOI: 10.1007/s40430-020-02727-2
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic study of the high-speed oblique water entry of a stepped cylindrical-cone projectile

Abstract: High-speed oblique water entry is an interesting subject, many physical aspects of which remain unknown up to now. Among high-speed air-to-water projectiles, the supercavitating cylindrical-cone (SCC) ones have economic and operational advantages over the other types. However, maintaining stability of the SCC projectiles inside the cavity at shallow entry angles is a challenging issue from both practical and design-related points. The first section of the present study proposes a novel and unique scheme of air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Zhao et al [29] studied the tail-slapping law of underwater projectiles with a speed of less than 50 m/s by MATLAB simulation. In addition, by means of computer numerical simulation technology, Akbari et al [30] adopted the numerical simulation method to study the process of oblique water-entry of the stepped head projectile, and briefly described the tail-slapping phenomenon, which mainly analyzed the motion law of the projectile. The next year, they (Akbari et al, [31]) conducted studies on the projectile motion characteristics of water entry under different length-diameter ratios and established the connection between the length-diameter ratio of the projectile and the motion stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al [29] studied the tail-slapping law of underwater projectiles with a speed of less than 50 m/s by MATLAB simulation. In addition, by means of computer numerical simulation technology, Akbari et al [30] adopted the numerical simulation method to study the process of oblique water-entry of the stepped head projectile, and briefly described the tail-slapping phenomenon, which mainly analyzed the motion law of the projectile. The next year, they (Akbari et al, [31]) conducted studies on the projectile motion characteristics of water entry under different length-diameter ratios and established the connection between the length-diameter ratio of the projectile and the motion stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by means of computer numerical simulation technology, Akbari et al [30] adopted the numerical simulation method to study the process of oblique water-entry of the stepped head projectile, and briefly described the tail-slapping phenomenon, which mainly analyzed the motion law of the projectile. The next year, they (Akbari et al, [31]) conducted studies on the projectile motion characteristics of water entry under different length-diameter ratios and established the connection between the length-diameter ratio of the projectile and the motion stability. Gu et al [32] obtained the weight parameters of the supercavitating projectile and summarized the influence of the weight parameters on the motion characteristics of the tail-slapping.…”
Section: Introductionmentioning
confidence: 99%
“…Ishchenko et al [8] shot supercavitating projectiles into water at an initial speed of nearly 1000 m/s, and analyzed the structural deformation phenomenon caused by the huge hydrodynamic force. Akbari et al [9] studied the hydrodynamic characteristics of supercavitating projectiles launched obliquely into water, and found that the supercavitating projectiles were subjected to a significant normal impact force which was closely related to the wet area. The experimental results of Chen et al [10] showed that supercavitating projectiles could fly stably in a tail-slap mode, indicating that an approximately periodic hydrodynamic force acts on the supercavitating projectile during the underwater motion process.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many experimental and numerical studies have investigated the flow characteristics of cavitation [7][8][9][10]. Knapp [11] observed and analyzed cloud cavitation flow and pointed out that the re-entrant flow from the closed cavity position is the cause of cloud cavitation ruptures.…”
Section: Introductionmentioning
confidence: 99%